Aluminium-lithium alloy composites using a powder metallurgy process - Lee, Hui Fung. (2009)
The performance requirement of advanced aerospace systems necessitates the development of new materials with superior properties. An Al Li alloy SiCp composite fulfils the above mentioned requirement, yielding a metal matrix composite with improved properties including modulus, coefficient of thermal expansion (CTE), damping capacity, wear resistance and increased-temperature performance. A powder metallurgy process involving a high pressure isostatic compaction, followed by a hot extrusion consolidation process was used.